1997
DOI: 10.1097/00003446-199704000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Description and Primary Results from an Audiometric Study of Male Twins

Abstract: These data reflect typical age-related deterioration in hearing ability accompanied by greater individual differences in hearing function with age. Across all ages, genetic and environmental effects are important sources of variation in hearing. However, preliminary analyses suggest that the relative influence of environment increases with age. These environmental effects are of the nonshared type that are not associated with shared family environments but rather are explained by unique exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 3 publications
0
73
3
2
Order By: Relevance
“…Presbycusis does cluster in families [35] and heritability estimates indicate that 35-55% of the variance of ARHL is attributable to the effects of genes: A Swedish study consisting of 250 monozygotic and 307 dizygotic male twins (aged 36-80) showed a heritability of 47% for the population above 65, using both questionnaire and audiometric data [36]. Using the same analytical method, the National Academy of Science-National Research Council (NAS-NRC) ageing twin panel study in the USA has estimated the heritability at 61% [37].…”
Section: Heritability Allelism and Genetic Modifiers Of Presbycusismentioning
confidence: 99%
See 1 more Smart Citation
“…Presbycusis does cluster in families [35] and heritability estimates indicate that 35-55% of the variance of ARHL is attributable to the effects of genes: A Swedish study consisting of 250 monozygotic and 307 dizygotic male twins (aged 36-80) showed a heritability of 47% for the population above 65, using both questionnaire and audiometric data [36]. Using the same analytical method, the National Academy of Science-National Research Council (NAS-NRC) ageing twin panel study in the USA has estimated the heritability at 61% [37].…”
Section: Heritability Allelism and Genetic Modifiers Of Presbycusismentioning
confidence: 99%
“…Heritability index was high in pairings of women (sister-sister, 0.53; mother-daughter, 0.36). Because of the difficulty of studying an outbred and older human population that includes intrinsic and environmental variables accumulated over the course of a lifetime [36,38], most studies have identified ARHL genes in a laboratory setting using mouse models, in which rigorous genetic and experimental control can be achieved, such that age is the most significant factor in an animal model of ARHL.…”
Section: Heritability Allelism and Genetic Modifiers Of Presbycusismentioning
confidence: 99%
“…Such variables do not lend themselves easily to retrospective quantification. Similarly, variability in age of onset, progression, and severity of AHL may be influenced by genetic factors (Gates et al, 1999;DeStefano et al, 2003) and heterogeneity in underlying pathology (Schuknecht and Gacek, 1993), as well as the variable contribution of other insults accumulated over the course of a lifetime (Lutman and Spencer, 1990;Karlsson et al, 1997). This variability has complicated our conduct and interpretation of investigations of NIHL and AHL in humans.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The involvement of genetic factors in the development of this multifactorial disorder was demonstrated by several heritability studies. [3][4][5] Only recently have the first studies aiming at the identification of these genetic factors been conducted. Hitherto, three linkage studies have been performed, [6][7][8] but only one region on chromosome 8q24.13-q24.22 reached genomewide significance.…”
Section: Introductionmentioning
confidence: 99%